Analisa Motivasi Kerja dan Lingkungan Kerja serta dampaknya terhadap Produktivitas Kerja Karyawan - Iklima Tiara Ananda Nugraha, Geulis; Ferdian, Ary (Jurnal Etnik: Ekonomi-Teknik, 2022)
Government institutions must be able to increase the productivity of their employees because in government and private institutions productivity is needed to achieve the goals that have been determined from the start, and employees play an important role to achieve these goals. Based on the Achievement of Productivity Programs and Activities, the productivity of the employees of the Bandung Regency RPRA Secretariat has decreased, this productivity in some previous literature is influenced by work motivation and work environment. The purpose of this study was to determine work motivation and work environment at the Bandung Regency RPRA Secretariat and to determine the effect of work motivation and work environment on work productivity at the Bandung Regency RPRA Secretariat either simultaneously or partially. This study uses quantitative methods with descriptive analysis techniques and multiple linear regression analysis. The sampling technique is a saturated sample with 67 respondents. This research was assisted by the IBM SPSS 24 program. The result of this research is that work motivation has a partial effect on work productivity, while the work environment variable does not partially affect work productivity. Meanwhile, work motivation and work environment partially affect work productivity.